Analisis Strategi Branding Dalam Pemasaran Digital Maire Homewear Untuk Meningkatkan Brand Awareness - Ivan Sanjaya; Iswati Iswati; Siti Aisah (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to analyze the branding strategy in digital marketing carried out by Maire Homewear through Instagram and Shopee platforms in an effort to increase brand awareness. Maire Homewear is a Micro, Small, and Medium Enterprise (MSME) engaged in the fashion sector with a flagship product in the form of patchwork daster. The focus of this study includes the branding strategy implemented, the obstacles encountered in its implementation, and the effectiveness of the strategy in building brand awareness among consumers. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Informants in this study consisted of the owner of Maire Homewear, two resellers, and two consumers. Data analysis was conducted using the Miles and Huberman model which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Maire Homewear's branding strategy is still stronger in the offline realm, such as through the reseller system and participation in various exhibitions. Meanwhile, the utilization of digital marketing through Instagram and Shopee is considered less than optimal. Content shared on Instagram is still inconsistent, and interactive features such as live shopping on Shopee have not been maximized. This results in Maire Homewear's brand awareness remaining relatively low among the general public, although it has begun to build among loyal customers, both those who purchase directly from Maire and through its reseller network. This study recommends that Maire Homewear increase the consistency and variety of its digital content on Instagram, including customer testimonials, production processes, and educational content about its products. Furthermore, utilizing the live shopping feature on Shopee is expected to be a more interactive and effective promotional tool for building relationships with consumers and expanding market reach.